1995
DOI: 10.1152/ajpheart.1995.268.2.h802
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and subcutaneous microvascular oxygen tension in conscious Syrian golden hamsters

Abstract: Arteriolar and venular oxygen tension distribution was studied in the subcutaneous connective tissue of the chamber window preparation in conscious Syrian golden hamsters as a function of the systemic PO2, PCO2, pH, arterial pressure and hematocrit, microvascular red blood cell (RBC) velocity, vessel diameter, and blood flow in the same microvessels. PO2 was measured with the phosphorescence decay technique using Pd-meso-tetra(4-carboxyphenyl)porphyrin (30 mg/kg body wt iv). Systemic arterial and venous PO2s w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
69
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 0 publications
9
69
1
Order By: Relevance
“…the kidney). The relative number of arteriolar vessels is high enough that some authors have suggested that a major source for oxygen transport in some tissues is the arterioles, rather than the capillaries (Ellsworth and Pittman, 1990;Kerger et al, 1995;Torres et al, 1996). Longitudinal gradients also exist in normal tissues, but, because of the redundancy of vascular supply, such gradients do not lead to vascular or tissue hypoxia in most cases (Duling and Berne, 1970;Ellsworth et al, 1987;Swain and Pittman, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…the kidney). The relative number of arteriolar vessels is high enough that some authors have suggested that a major source for oxygen transport in some tissues is the arterioles, rather than the capillaries (Ellsworth and Pittman, 1990;Kerger et al, 1995;Torres et al, 1996). Longitudinal gradients also exist in normal tissues, but, because of the redundancy of vascular supply, such gradients do not lead to vascular or tissue hypoxia in most cases (Duling and Berne, 1970;Ellsworth et al, 1987;Swain and Pittman, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution microvascular PO2 measurements were made using phosphorescence quenching microscopy, which has been described in greater detail elsewhere (12). Oxygen measurements are based on the oxygen-dependent quenching of phosphorescence emitted by an albumin-bound metalloporphyrin complex after light excitation.…”
Section: Methodsmentioning
confidence: 99%
“…Data are given as means Ϯ SD for the indicated number of animals. Data were analyzed by using analysis of variance, followed by Fisher's protected leastsignificant difference test between the groups according to the previous studies (11,12,24). Student's t-test was used for the comparisons within each group.…”
Section: Methodsmentioning
confidence: 99%